Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1159/000083917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 1 Diabetes among 6- to 18-Year-Old Kuwaiti Children

Abstract: Objectives: To determine the prevalence of type 1 diabetes among 6- to 18-year-old Kuwaiti children according to gender, age, and region. Subjects and Methods: Children with type 1 diabetes aged 6–18 years were identified at 182 schools (50 primary, 63 intermediate, and 69 secondary) in Kuwait during the study period October 2000 to September 2002. Schools were randomly selected using the 2000/01 educational districts’ registers as sampling frame proportional to the number of schools in each district. Prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
3
18
2
Order By: Relevance
“…Our recently published study (21) on T1DM incidence in Diyarbakır showed an incidence lower than in northern Europe, the United States, Australia, Canada, New Zealand, and rich Middle Eastern countries like Kuwait and Saudi Arabia, whereas it was similar to rates in neighboring countries or nearby Balkan states and some South American countries, like Chile (7-8/10 5 ) and Brazil (6.3-10/10 5 ) (4,6,7,10,(30)(31)(32)(33)(34). Similarly, the prevalence of T1DM detected in the present study among school children 6-18 years old in Diyarbakır, a city of the SAR of Turkey, was lower than those in the USA, North Europe, and rich Middle Eastern countries like Kuwait and Saudi Arabia, while being higher than in most Asian countries and similar to that of the Balkan states and Mediterranean countries, excluding the Sardinia region in Italy (10,24,(35)(36)(37)(38). In the present study, the prevalence of T1DM was higher in girls (0.47/10 3 ) than boys (0.37/10 3 ), and this was consistent with previously published data from our clinic (21).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our recently published study (21) on T1DM incidence in Diyarbakır showed an incidence lower than in northern Europe, the United States, Australia, Canada, New Zealand, and rich Middle Eastern countries like Kuwait and Saudi Arabia, whereas it was similar to rates in neighboring countries or nearby Balkan states and some South American countries, like Chile (7-8/10 5 ) and Brazil (6.3-10/10 5 ) (4,6,7,10,(30)(31)(32)(33)(34). Similarly, the prevalence of T1DM detected in the present study among school children 6-18 years old in Diyarbakır, a city of the SAR of Turkey, was lower than those in the USA, North Europe, and rich Middle Eastern countries like Kuwait and Saudi Arabia, while being higher than in most Asian countries and similar to that of the Balkan states and Mediterranean countries, excluding the Sardinia region in Italy (10,24,(35)(36)(37)(38). In the present study, the prevalence of T1DM was higher in girls (0.47/10 3 ) than boys (0.37/10 3 ), and this was consistent with previously published data from our clinic (21).…”
Section: Discussionsupporting
confidence: 54%
“…Although T1DM is observed in equal rates in general in girls and boys, it is reported in some studies that it was more common in girls than in boys (10). It is reported to be higher in males in countries with high incidences, and higher in females in countries with low incidences (10,35,(39)(40)(41). The low T1DM incidence observed in our region could explain the higher prevalence of T1DM in girls.…”
Section: Discussioncontrasting
confidence: 46%
“…Surprisingly, only 30.8% of pedodontists had an adequate knowledge about the effect of diabetes on periodontal health. This percentage is considered to be very low compared to the prevalence of diabetes among children in Kuwait [21,29] . Recent studies have shown that accelerated periodontal destruction in children with diabetes is related to poor metabolic control since periodontal destruction can start very early in life and becomes more prominent as diabetic children become adolescents [5] .…”
Section: Discussionmentioning
confidence: 93%
“…It is reasonable to assume that vessel and connective tissue alterations as well as the impairment of the immune system and other associated metabolic changes caused by diabetes play an important role. DM is common in Kuwait; about 15% of the adult Kuwaiti population has type 2 diabetes [3] and the prevalence of type 1 diabetes is 269.9 per 100,000 Kuwaiti children [4] . Although diabetes is common in Kuwait, systematic surveys of the cutaneous manifestations in diabetic patients are lacking.…”
Section: Introductionmentioning
confidence: 99%